A Simple Techno-Economic Assessment for Scaling-Up the Enzymatic Hydrolysis of MSW Pulp - Climent Barba, Fernando; Grasham, Olivier; Puri, Dhivya J.; Blacker, A. John (Frontiers in Energy Research, 2022)
A techno-economic assessment (TEA) of enzymatic hydrolyses of a municipal solid waste (MSW) derived pulp was performed, to compare various bioprocessing configurations (two-stage continuous, batch and two-stage fed-batch) for the production of platform sugars at both pilot and demonstration-scale. The modelled configuration used either rotary drum and/or continuous stirred tank reactors . By using reaction kinetics and public vendor’s quotes, economic analyses including: : Capital Expenditure (CapEx); Operation Expenditure (OpEx); Revenue and Profit; Return on Investment (ROI); Payback Period (PP), were calculated for each of the proposed system. The TEA showed that a two-stage continuous configuration with a total residence time of 54 hours (6 and 48 hours for primary and secondary stage) was the best option for obtaining sugars, showing 7-fold higher enzyme productivity and better profit than the reference systems. Although, the analysis of pilot-scale the enzymatic hydrolysis demonstrated an unprofitable process this was due mainly to the high associated enzyme cost. Increasing the scale diminished this problem leading to higher profit per processed unit (£/kg lignocellulosic sugars). From an investment perspective, the two stage 6/48 configuration gave a more attractive ROI and PP than the other designs.